2018
DOI: 10.1016/s1473-3099(18)30278-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of targeted enhanced terminal room disinfection on hospital-wide acquisition and infection with multidrug-resistant organisms and Clostridium difficile: a secondary analysis of a multicentre cluster randomised controlled trial with crossover design (BETR Disinfection)

Abstract: Summary Background The hospital environment is a source of pathogen transmission. The effect of enhanced disinfection strategies on the hospital-wide incidence of infection has not been investigated in a multicentre, randomised controlled trial. We aimed to assess the effectiveness of four disinfection strategies on hospital-wide incidence of multidrug-resistant organisms and Clostridium difficile in the Benefits of Enhanced Terminal Room (BETR) Disinfection study. Methods We did a prespecified secondary an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
2
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 27 publications
1
91
2
6
Order By: Relevance
“…Patients admitted to rooms disinfected using UVC were significantly less likely to acquire MRSA and VRE when admitted to rooms where the previous occupant had these pathogens; there was no significant reduction in C. difficile infections. A reanalysis of data from the same study evaluated whole-hospital outcomes, and found a significant reduction in VRE and C. difficile [122]. Several before-after studies have shown that adding UVC to disinfection protocols reduces the transmission of MDROs [123,124].…”
Section: Uvc Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients admitted to rooms disinfected using UVC were significantly less likely to acquire MRSA and VRE when admitted to rooms where the previous occupant had these pathogens; there was no significant reduction in C. difficile infections. A reanalysis of data from the same study evaluated whole-hospital outcomes, and found a significant reduction in VRE and C. difficile [122]. Several before-after studies have shown that adding UVC to disinfection protocols reduces the transmission of MDROs [123,124].…”
Section: Uvc Systemsmentioning
confidence: 99%
“…Study performed over a long period; changes made in MRSA diagnostic protocols. Anderson [122] UVC Cluster RCT Significant MDRO acquisition reduction on the hospital level Monitored potential confounders Anderson [12] UVC Cluster RCT Significant MDRO acquisition reduction on an individual level Monitored potential confounders Pegues [124] UVC 2 yr before-after Significant reduction in C. difficile compared with control wards…”
Section: H 2 O 2 Vapormentioning
confidence: 99%
“…Environmental cleaning and disinfection. Environmental cleaning has been shown to be an integral part of CDI prevention (18,19). Enhanced cleaning practices in enteric precautions rooms include the use of an EPA-registered cleaner with known sporicidal activity during daily cleans and at patient discharge.…”
Section: Methodsmentioning
confidence: 99%
“…The 2017 SHEA/IDSA guidelines also highlight the role of terminal room cleaning with a sporicidal agent, with consideration of daily sporicidal room cleaning in hyperendemic settings . So‐called no‐touch disinfection technologies showed promise in several studies to reduce C. difficile spores and CDI incidence, and, recently, the use of ultraviolet light disinfection of rooms induced a prolonged CDI‐free interval in a burn ICU . Unfortunately, the available analyses for these automated methodologies had significant limitations when the SHEA/IDSA guideline was released, leading the expert panel to conclude that no recommendation could be made regarding their incorporation into a CDI prevention program …”
Section: Prevention Of Transmissionmentioning
confidence: 99%
“…11 So-called no-touch disinfection technologies showed promise in several studies to reduce C. difficile spores and CDI incidence, and, recently, the use of ultraviolet light disinfection of rooms induced a prolonged CDI-free interval in a burn ICU. 17,18 Unfortunately, the available analyses for these automated methodologies had significant limitations when the SHEA/IDSA guideline was released, leading the expert panel to conclude that no recommendation could be made regarding their incorporation into a CDI prevention program. 11 Robust hand hygiene programs should be foundational in every ICU and include objective components such as so-called secret shopper audits (anonymous trained observers who monitor hand hygiene practices), volumebased utilization of hand disinfectants, and routine feedback for ICU staff.…”
Section: Prevention Of Transmissionmentioning
confidence: 99%